DSI advantage capability of LFR - Shah, Asadullah; Abdullah Zammarh, Nuha (IIUM Press, 2011)
The Digital Speech interpolation (DSI) advantage is signal processing technique, using this technique one can maximise the systems efficiency, such as a telephonic system capability to accommodate more users due to the non-active parts within speech signal. By utilising non activity parts along with Lost Frame Reconstruction (LFR), higher DSI advantage can be achieved. By doing so more users can be allowed in the system. In this chapter both DSI and LFR are explained to how one can make use ofthese signal processing techniques to increase the performance ofthe system